Evaluation of pre-screened sweet potato germplasm for biomass production under different cropping regimes and their potential as dual-purpose varieties in Kenya. - Kinyua, J.; Lukuyu, Ben A.; Agili, S.; Gachuiri, C.K.; Low, Jan W. (2011)
Six cultivars of sweet potato were grown on farms in five sites located in central, south and north rift valley regions of Kenya under rain fed conditions. Two sites each were located in the high and medium altitude areas while one was located in the low altitude area. All sites have warm climates except one in the high altitude that experiences cold climate. The cultivars included 103001, Gweri, Kemb 23, Kemb 36, Naspot 1 and Wagabolige. The vines of each variety were harvested at two different stages (75 and 150 days) post planting. The 75-day treatment was ratooned again at 150 day post planting. Agronomical observations were carried during the long rains seaso 2010. Harvesting vines twice significantly (P<001) increased forage yields but significantly (P<001) reduced root yield in all varieties. The Gweri variety realized the highest forage but lowest storage root yields indicating its potential as a forage variety. Kemb 23, Kemb 36 and Napsot 1 produced appreciable amount of vines and highest root storage yield making them potential dual purpose varieties. The effect of agro ecological zone (AEZ) varied with time of harvest. There was less interaction between the cultivars and the AEZ at 75 day harvest. Gweri, Kemb 23 and Kemb 36 showed some level of interaction with AEZ at 150 day harvest. Across AEZs dry vine yields (t DM/ha) ranged from 2.3,5.3 in 103001, 2.4,8.5 in Gweri, 1.9,8.4 in Kemb 23, 1.4,7.8 in Kemb 36, 1.8,7.4 in Naspot 1 and 1.2,7.4 in Wagabolige and dry storage root yields (t DM/ha) ranged from 0.7,2 in 103001, 0.3,1.2 in Gweri, 0.4,2.5 in Kemb 23, 0.9,1.5 in Kemb 36 , 1.7,2.3 in Naspot 1 and 0.5,1.8 in Wagabolige. The storage root yield: vine (R/V) ratio was determined by dividing the total root by vine dry matter yield. The R/V ratios significantly (P<005) varied between cultivar and harvesting stage. The mean R/V were 1.8 in 103001, 0.2 in Gweri, 0.6 in Kemb 23, 0.5 in Kemb 36, 1.5 in Naspot 1 and 0.7 in Wagabolige. The R/V ratios obtained classifies 103001 and Naspot 1 as low forage-high root production varieties, Wagabolige and Kemb 36 as low dual purpose and Kemb 36 and Gweri as forage varieties. Preference of different growers for forage vs. dual purpose types appears to vary by location.